Comparative studies on physicochemical characterisation, antioxidant and antibacterial activity of chitosan extracted from Scylla paramamosain and Penaeus monodon shells - Wan Roslina Wan Yusof,; Muhd Amir Asyraf Noh,; Nor Aimuni Abd Aziz,; Noorasmin Mokhtar Ahmad,; Awang Ahmad Sallehin Awang Husaini, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Marine shells are commonly discarded as waste. However, they could be used to extract a multi versatile polymer, chitosan. As one of the marine by-products, chitosan can be found in the exoskeleton of crustaceans via the deacetylation process of chitin. This project aimed to investigate and compare the physicochemical and biological properties of chitosan extracted from two marine organisms because the properties depend upon the chitin source. In brief, chitosan was extracted through chemical processes from mud crab, Scylla paramamosain and prawn, Penaeus monodon shells. The percentage yield, moisture, solubility, water binding capacity and fat binding capacity of the extracted chitosan were determined. The degree of deacetylation and SEM images of the extracted chitosan were obtained. The antioxidant and antibacterial properties in both chitosan were evaluated. The results showed that chitosan from S. paramamosain shells has a higher percentage yield, moisture content, water binding capacity, fat binding capacity and degree of deacetylation compared to chitosan from P. monodon shells. In antioxidant assays, chitosan from S. paramamosain shells showed higher scavenging activity (22.2%) than chitosan from P. monodon shells (6.7%). In disk diffusion assay, chitosan from S. paramamosain shells displayed antibacterial activity against E. coli and S. aureus, while chitosan from P. monodon shells showed no activity. Thus, the study showed that S. paramamosain shells could be used as a starting material to produce valuable chitosan with high potential of its biological activities.